1991
DOI: 10.1111/j.1744-6570.1991.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

The Perils of Participation: Effects of Choice of Training on Trainee Motivation and Learning

Abstract: This study presents an empirical test of the effects of trainee choice of training on subsequent motivation and learning. 207 trainees were randomly assigned to one of three conditions: (a) no choice of training; (b) choice of training-but choice not received; (c) choice of trainingwith choice received. A pilot study was used to create a unique training context whereby trainees could be differentiated on the three conditions of choice, while all ultimately received the identical training module. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
243
4
7

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(267 citation statements)
references
References 16 publications
(15 reference statements)
13
243
4
7
Order By: Relevance
“…In particular, there have been a number of studies that have shown that training motivation is related to trainee reactions (e.g., Mathieu et al, 1992;Tannenbaum et al, 1991), learning (e.g., Baldwin et al, 1991;Clark, 1990;Hicks, 1984;Mathieu et al, 1992), performance/transfer (e.g., Baldwin et al, 1991;Facteau, Dobbins, Russell, Ladd, & Kudisch, 1992;Ralls & Klein, 1991), and completion of training (Biersner et al, 1977;Mobley et al, 1979).…”
Section: Technical Report 93-011mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, there have been a number of studies that have shown that training motivation is related to trainee reactions (e.g., Mathieu et al, 1992;Tannenbaum et al, 1991), learning (e.g., Baldwin et al, 1991;Clark, 1990;Hicks, 1984;Mathieu et al, 1992), performance/transfer (e.g., Baldwin et al, 1991;Facteau, Dobbins, Russell, Ladd, & Kudisch, 1992;Ralls & Klein, 1991), and completion of training (Biersner et al, 1977;Mobley et al, 1979).…”
Section: Technical Report 93-011mentioning
confidence: 99%
“…Baldwin et al (1991) found that trainees who were asked to specify training preferences, but were subsequently assigned to a different type of training, exhibited lower motivation to learn than those trainees who were not asked for their preferences at all.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Employee motivation argument is that action learning opportunities make the work more interesting (Knudsen, & Smith, 1934;Wagner, & Gooding, 1987;Baldwin, Magjuka, & Loher, 1991;McGill, & Beaty, 2001). According to Fernet, Senecal, Guay, Marsh and Dowson (2008), action learning is a potential solution to employees' lack of motivation as specific work tasks with some challenging problems improve the self-efficacy and self determination of employees as well as reduce the job burnout and turnover intensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to how voice should be solicited, the genuineness of the voice solicitation is of critical concern. If participants feel that a decision maker fails to give participant input adequate consideration, or if the voice solicitation is perceived as disingenuous, the outcome is likely to be frustration and resentment (e.g., Baldwin, Magjuka, & Loher, 1991;Folger, 1977).…”
mentioning
confidence: 99%